Reliability Factors in Adverse Drug Reaction Reporting - Marlin, R. L. (Methods of Information in Medicine, 1981)
In the process of utilizing marketed pharmaceutical preparations, a primary concern of researchers, physicians, industry and government agencies is the occurrence of adverse reactions.The purpose of this research was to devise and test a method of evaluating the FDA’s voluntary system for collection of adverse reactions that occur during hospitalization, as a form of communicating valid data. The Federal Government generates data and as such becomes an originator of instructions, specifications/ directives for job and/or projects within its bureaucratic structure. These descriptions (»Guidelines«) of responsibilities regulate the activities of all systems.The objectives of this study were to determine whether the guidelines established by the issuing agency (FDA) were interpreted in a uniform manner with those individuals who generate the data (hospital coordinators) and to determine if factors external to the system affect the reporting.Three phases were employed:1. Review of data in a baseline year,2. A survey questionnaire to all hospital coordinators and FDA personnel involved in the system,3. Interviews with a conveniently selected sample of coordinators.The findings showed that the guidelines were interpreted differently by the coordinators and the FDA personnel. The study also demonstrated that the external factors such as legality, »defensive medicine«, various definitions of the term »adverse drug reaction«, individual bias and FDA feedback all affect participation in the program. It is also affected by the poorly coordinated education and orientation programs of the FDA and attitudes affecting patient care.Detailed instructions to participants on the procedures, purposes and goals of a collection program, with communication feedback to and from the agency and the generators, are important facts in maintaining voluntary participation.
Keywords: Adverse Reactions; Drug Reactions; Communications; FDA Reporting; Government Regulations; Drug Monitoring